The economist’s job - Alessandro Roncaglia (PSL Quarterly Review, 2018)
The short editorial introduces the new issue and volume of the Review. In this issue, the PSL Quarterly Review is relaunching the “Recollections of Eminent Economists” series, which used to be published in both English and Italian, respectively in BNL Quarterly Review and Moneta e Credito. The “Recollections of Eminent Economists” series was launched in 1978, with the first article in September 1978 by John Hicks. The Recollections were intended as a series of autobiographies of intellectuals. Authors invited to contribute were allowed full liberty of topic and scope. ). As before, authors invited to contribute to the new series are granted the maximum creative liberty; the articles may be autobiographical, or consist in reflections on their research, or, more generally, on economics as a discipline. The first inaugural contribution published in this issue is by board member A.P. Thirlwall.